Pengaruh Kinerja Petugas Apron Movement Control (AMC) Terhadap Kedisiplinan Kerja Petugas Ground Handling Di Apron Bandar Udara Internasional Yogyakarta - Mohammad Doni Saputra; Ary Subiyantoro; Nurhadi Nugroho; Saimin (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2026)
This study aims to determine how the performance of Apron Movement Control officers influences the discipline of Ground Handling officers on the apron of Yogyakarta International Airport. The method in this study is a quantitative descriptive method. Data analysis techniques use validity tests, reliability tests, simple regression tests, determination tests, and t tests. Based on the results of the study, the results of the hypothesis obtained were the t-value of officer performance was 1.920> t table 1.677 with a probability of 0.000 <0.05, which means that there is a significant influence of AMC officer performance on the discipline of Ground Handling officers. From the results of the determination coefficient test, it shows that the R Square value is 0.754. This means that the magnitude of the influence of the AMC officer performance variable on the discipline of Ground Handling officers on the apron of Yogyakarta International Airport is 75.4%, while the remaining 24.6% must be explained by other causal factors that come from outside this regression method.